At the Intersection of Cultural Cosmopolitanism and Spatial Literary Studies - Thornbury, Barbara (Migrating Minds)
Review article - Geo-Spatiality in Asian and Oceanic Literature and Culture: Worlding Asia in the Anthropocene, ed. by Shiuhhuah Serena Chou, Soyoung Kim, and Rob Sean Wilson. Cham, Switzerland: Palgrave Macmillan, 2022, 323 p., ISBN: 978-3-031-04046-7 Spatiality at the Periphery in European Literatures and Visual Arts, ed. by Kathryn Everly, Stefano Giannini, and Karina von Tippelskirch. Cham, Switzerland: Palgrave Macmillan, 2023, 212 p., ISBN: 978-3-031-30311-1 Spatial Literary Studies: Interdisciplinary Approaches to Space, Geography, and the Imagination, ed. by Robert T. Tally Jr. New York: Routledge, 2020, 352 p., ISBN: 978-1-003-05602-7